Framing the direction of environmental peformance using theory of dynamic capabilities - Appannan, Jeya Santhini; Mohd Said, Ridzwana; Ong, Tze San; Senik, Rosmila (Sciendo, 2019)
Considerable interest of environmental studies has appeared in the literature over the past decade. Environmental performance indicates a way to minimize environmental damages caused by business activity. It is evident that good environmental performance signals wise protection of the natural environment. However, it is still not entirely understood the factors that affect the environmental performance. As such, the purpose of this paper is to examine factors that contribute to the environmental performance utilizing the theory of Dynamic Capabilities and investigate the body of literature constituting the field. The outcome of this study is expected to provide useful direction for the policy makers and companies to combat environmental issues.